Estimulación temprana y su impacto en el desarrollo motriz de los niños del subnivel 2, en la Escuela de Educación Básica Oswaldo Villamil Auz de la Parroquia Viva Alfaro, cantón Quevedo - Cevallos Gutierrez, Nelly Jajaira (2021)
The purpose of this research is to analyze early stimulation and its impact on the motor development of children in Sub-level two of the “Oswaldo Villamil Auz” Basic Education School located in the Viva Alfaro parish, Quevedo canton, in the school period 2021-2020. To determine the characteristics of the variables, scientific articles and research from the international and national context, from primary sources, were used. The theory of the Stages of Jean Piaget and the method of Glen Doman with reference to the object of study. The population considered is 60 students enrolled in sublevel two and 5 teachers of Initial Education. The applied methodology is descriptive, exploratory and bibliographic. The information gathering techniques are the closed question survey carried out with the parents, the semi-structured interview with the teachers. Whose results determines that it is important to carry out a training plan in relation to early stimulation aimed at the educational community that includes sub-level two.